The Yugoslav perspective on Italian Eurocommunism in the second half of the 1970s - Dragišić Petar (Balcanica, 2022)
The article outlines the key elements of the Yugoslav perceptions of the Italian Communist Party’s (PCI) ideological and political orientation during its Eurocommunist phase. In addition, it investigates the relationship between the League of Communists of Yugoslavia and PCI in the latter half of the 1970s. The article is primarily based on an analysis of Yugoslav archival sources and press materials.